Changes in Hepatitis C Awareness in Different Disciplines During COVID-19 - Barutçu, Sezgin; Yıldırım, Çiğdem; Yıldırım, Abdullah Emre; Konduk, Buğra Tolga; Abidin Sayiner, Zeynel; Gülşen, Murat Taner (Turkish Journal of Gastroenterology, 2022)
Background: We aimed to determine the awareness of referring hepatitis C virus patients to the relevant departments and the effect of the pandemic period on this subject. Methods: A total of 65 743 patients with anti-hepatitis C virus requests before and during the COVID-19 pandemic were retrospectively screened. Anti-hepatitis C virus-positive patients were divided into 5 groups according to age distribution. The distribution of patients with anti-hepatitis C virus positivity was compared according to age groups, before and during COVID-19. Anti-hepatitis C virus-pos- itive patients who were not requested hepatitis C virus RNA were evaluated individually according to the departments, and hepatitis C virus awareness was compared before and during COVID-19. Results: Anti-hepatitis C virus positivity rate was 1.54% before COVID-19; this rate was 2.15% during COVID-19. When the anti-hep- atitis C virus positivity rate was compared in terms of age distribution according to before and during COVID-19, it was observed that there was a statistically significant decrease in the >65 age group in the COVID-19 period (P = .004). It was found that 216 (32%) of the patients who had anti-hepatitis C virus (+) before COVID-19 and 231 (48.1%) of the patients during COVID-19 were not requested hepatitis C virus RNA test (P < .0001). The departments with the highest awareness of hepatitis C virus were gastroenterology, infec- tious diseases, hematology, gynecology and obstetrics, and oncology, while the departments with the lowest hepatitis C virus awareness were ophthalmology, psychiatry, and general surgery. It was found that chronic hepatitis C virus awareness decreased in all departments during COVID-19. Conclusion: Hepatitis C virus awareness has decreased in all medical departments despite the physician alert system during COVID-19 and also the rate of anti-hepatitis C virus (+) patients decreased in the group aged >65 years during the pandemic. Cite this article as: Barutçu S, Yıldırım Ç, Yıldırım AE, Konduk BT, Sayiner ZA, Gülşen MT. Changes in hepatitis C awareness in different disciplines during COVID-19. Turk J Gastroenterol. 2022;33(10):838-843.